HUBUNGAN KARAKTERISTIK INDIVIDU, BERAT BEBAN DAN FREKUENSI ANGKUT DENGAN PENYAKIT THORACIC OUTLET SYNDROME PADA BURUH ANGKUT DI PASAR COMAL - Wiwik Widiyanti; Siswi Jayanti; Ida Wahyuni (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2018)
Thoracic Outlet Syndrome (TOS) is a various kinds of symptoms which caused by the suppression of the nerves and blood vessels in the upper part of the first rib and behind the collarbone. The symptoms of TOS are pain in shoulders, arms, numb, weak grip, and the pale fingers. The interview resulted that porters in Comal market felt the symptoms such as pain in shoulders, arms, tingling, and shoulders felt throbbing. The aim of research was to analyze the relation between individual characteristics, weight of load, and frequency of transport with Thoracic Outlet Syndrome (TOS). The research method used was explanatory with cross sectional design. The sample was the entire population of 32 porters in Comal Market. Thoracic Outlet Syndrome (TOS) measured by the roos test method and weight of load measured by floor scale. The results showed that porters who experienced TOS were 68,8%, risky age (56,2%), long working period (78,1%), obesity (15,6%), risky weight of load (78,1%), and high transport frequency (65,6%).The result of chi-square analysis showed there was relation between age (p = 0,019), weight of load (p = 0,019), and frequency of transport (p = 0,013) with the Thoracic Outlet Syndrome (TOS). While there was no relation between work period (p = 0,648) and nutritional status (p = 0,637) with Thoracic Outlet Syndrome (TOS). Based on the results of the study it was recommended that porters should not force themselves to carry loads exceed the limit, use transport devices.